Upaya Pencegahan Terhadap Anak Sebagai Pelaku Penyalahgunaan Minuman Beralkohol di Kota Pangkalpinang - Safitri, Nashva Azzahra Maharani; Agustian, Rio Armanda; Toni, Toni (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
Prevention efforts against children as perpetrators of alcohol abuse in Pangkalpinang City are preventive efforts that involve active cooperation between the government, schools, families and communities. This thesis aims to analyze efforts to prevent children as perpetrators of alcohol abuse in Pangkalpinang City and find out how efforts to overcome inhibiting factors in preventing children as perpetrators. The method used is juridical-empirical with a sociological juridical approach, data collection techniques through interviews, observation and literature study and data analysis is managed by qualitative analysis. The results of this study are the Civil Service Police Unit (Satpol PP) has implemented a night study hour patrol program to prevent children from wandering outside the home at night. The Education and Culture Office has also implemented counseling programs, teacher training, and the formation of Violence Handling and Prevention Teams (TPPK) in schools. The Lembaga Pembinaan Khusus Anak (LPKA) Class II Pangkalpinang also plays a role in fostering children involved in criminal cases, including alcohol abuse, through educational and religious programs. The obstacles faced include the large number of stores that sell alcohol freely, the lack of family supervision, and the lack of public awareness. Efforts to overcome them are carried out by routine surveillance patrols, disseminating information through visual media, and encouraging increased awareness and participation of parents and strengthening the role of the community in supervising and fostering children in their neighborhood.